Maternal side effects & fetal neuroprotection according to body mass index after magnesium sulfate in a multicenter randomized controlled trial. (17th January 2018) - Vilchez, Gustavo; Dai, Jing; Lagos, Moraima; Sokol, Robert J.
Abstract: Objective: Evidence supports the need of dose-adjustment of several drugs according to body mass index (BMI) to prevent toxicity in the underweight, and ensure efficacy in obese women. However, for MgSO4 neuroprotection, the effect of BMI on maternal toxicity and fetal neuroprotection is understudied. We analyze the effect of BMI on maternal/infant outcomes after MgSO4 . Methods: Secondary analysis of a clinical trial that studied MgSO4 neuroprotection. Maternal side effects, magnesium cord levels, and offspring cerebral palsy/death were analyzed along BMI strata using ANOVA and chi-square test. Logistic regression was used to calculate adjusted odds ratios according to the treatment and BMI, using nonobese that received placebo as reference. Interaction analyses were performed to validate differential efficacy of BMI. Results: From 2241 women, more side effects and higher magnesium cord levels were seen in underweight women ( p  = 0.05). MgSO4 neuroprotection was effective in the non-obese ( p  = 0.02), but not in obese women ( p  = 1.00). In multivariate analyses, MgSO4 significantly reduced cerebral palsy only in nonobese women. Interaction analyses showed the moderator effect of BMI ( p  = 0.169). Increasing MgSO4 dose in obese mothers may ensure neuroprotective efficacy without representing increased maternal risks. Considering costs of studying this association, current analysis may form the basis for reasonable practice.